Interleukin-1β provided by KIT-competent mast cells is required for KRAS-mutant lung adenocarcinoma. (3rd July 2019) - Lilis, Ioannis; Ntaliarda, Giannoula; Papaleonidopoulos, Vassilios; Giotopoulou, Georgia A; Oplopoiou, Maria; Marazioti, Antonia; Spella, Magda; Marwitz, Sebastian; Goldmann, Torsten; Bravou, Vasiliki; Giopanou, Ioanna; Stathopoulos, Georgios T.
ABSTRACT: Mast cells (MC) have been identified in human lung adenocarcinoma (LADC) tissues, but their functional role has not been investigated in vivo . For this, we applied three mouse models of KRAS- mutant LADC to two different MC-deficient mouse strains ( cKit Wsh and Cpa3.Cre ). Moreover, we derived MC gene signatures from murine bone marrow-derived MC and used them to interrogate five human cohorts of LADC patients. Tumor-free cKit Wsh and Cpa3.Cre mice were deficient in alveolar and skin KIT-dependent (KIT+) MC, but cKit Wsh mice retained normal KIT-independent (KIT-) MC in the airways. Both KIT+ and KIT- MC infiltrated murine LADC to varying degrees, but KIT+ MC were more abundant and promoted LADC initiation and progression through interleukin-1β secretion. KIT+ MC and their transcriptional signature were significantly enriched in human LADC compared to adjacent normal tissue, especially in the subset of patients with KRAS mutations. Importantly, MC density increased with tumor stage and high overall expression of the KIT+ MC signature portended poor survival. Collectively, our results indicate that KIT+ MC foster LADC development and represent marked therapeutic targets.